LEVEL OF DENTAL AND ORAL HEALTH KNOWLEDGE BASED ON CLINICAL STATUS MEASURED THROUGH THE DMF-T AND OHI-S INDEXES - Sri Purwanti; Aryandi Syaputra; Ervina Nurrahmah; Stefania Valentine Simanjuntak (Dentin, 2026)
ABSTRACT Background: The main problem often found in children is dental caries, which can develop into pulpitis. WHO data shows that caries is the biggest dental and oral problem globally with 60-90% of children experiencing dental caries. Pulpitis is defined as inflammation of the pulp tissue due to microbial, chemical, mechanical, or thermal irritation. One of the main causes is dental caries. Objective: The study aims to analyze the level of knowledge of dental and oral health as measured by the DMF-T and OHI-S indices. Method: The type of survey is Descriptive Observational with Cross Sectional method. The population of this study was students of SDN Telaga Biru 5 Banjarmasin, namely 61 students. The sample used a total sampling technique. Results: Distribution based on the Decay category was 125 teeth (85.03%), Missing was 13 teeth (8.84%), and Filling was 10 teeth (6.13%). The DMF-T index obtained from the DMF-T value of 61 students was 2.4 which categorized that the tooth decay that occurred was included in the low category. Distribution of dental and oral health examination results based on the OHI-S index of 61 students with a good category of 40 students (65.57%), a moderate category of 21 students (34.43%), and a poor category of 0 students (0%). Distribution of tooth brushing frequency results of 61 students with a very low category of 0 students, a low category of 2 students (3.3%), a moderate category of 39 students (64%), and a high category of 20 students (32.8%). Conclusion: The DMF-T index in 61 students is 2.4, which is categorized as low. The OHI-S index obtained from 40 students is categorized as good. The OHI-S index obtained from 21 students is categorized as moderate.  Keywords: Caries, Children's Health, Pulpitis